Peritoneal Tuberculosis in Infants: Diagnostic Challenges - Ndoye, Ndeye Aby; Mbaye, Papa Alassane; Tendeng, Jacques Noel; Cissé, Lissoune; Diao, Mamadou Lamine; Dieng, Mactar; Gueye, Doudou; Niang, Dibor; Ndour, Oumar; Ngom, Gabriel (European Journal of Pediatric Surgery Reports, 2018)
Abdominal tuberculosis is rare in immunocompetent infants. We report on two infants with peritoneal tuberculosis (6 and 8 months) who underwent laparotomy for suspected intussusception. In the first patient, characteristic lesions of peritoneal tuberculosis were observed intraoperatively with presence of multiple granulations. Tuberculin intradermal reaction (IDRt) was positive and tuberculous contagium could be cultured. In the second patient, the IDRt and GeneXpert tests were negative. In both patients, the histopathological examination of the biopsy specimens confirmed the diagnosis of peritoneal tuberculosis. The clinical courses under tuberculostatic therapy were favorable in both cases.
Keywords: peritoneal tuberculosis; infant; acute abdomen; laparotomy